ANALISIS PERKEMBANGAN PERBANKAN SYARIAH DI MALAYSIA (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This article discusses the development of Islamic banking in Muslim-majority countries, namely Malaysia. Malaysia was one of the first countries in Southeast Asia to establish an Islamic bank. The marketing management of Islamic banks in Malaysia is an interesting subject to study, this study uses a qualitative descriptive method, by taking several literature studies that are in accordance with the theme in accordance with the writing of this article. The existence of Islamic banks in Malaysia is strongly supported by the Malaysian government so that Islamic bank funds in Malaysia come from the government, namely 90 percent of government funds, while funds originating from the public are only around 10 percent. In general, the performance of Islamic banking continues to grow with a market share of 29% which can be seen from three indicators, namely the number of assets collected, the amount of financing disbursed by banks (PYD), and third party funds (DPK). In 2018, asset growth was 12.57%, PYD 12.17%, DPK 11.14%, 2019 asset growth 9.93%, PYD 10.89%, DPK 11.93%, and in 2020 asset growth 13 .11%, PYD 8.08%, and DPK 11.88% with total assets of 608.9 trillion, pyd 394.6, and dpk 475.8.